Intervention Strategy for Enhancing Livelihoods of Land Reform Farmers in Waterberg District, South Africa - Malose Moses Tjale; Marizvikuru Mwale; Beata M. Kilonzo (AGRARIS: Journal of Agribusiness and Rural Development Research, 2020)
ABSTRACTDespite implementation of various land reform policies in South Africa post 1994 to address poverty and inequality, poor performance of the restituted farms and unimproved livelihoods of farm beneficiaries still exist. Hence, the objective of the study was to develop an intervention strategy to improve livelihoods of farm beneficiaries in South Africa and beyond. Qualitative and quantitative studies were used to collect data from key stakeholders and farm beneficiaries from 32 farms in Waterberg District. Focus group discussions, non-participatory observation, interviews and feedback sessions were used to collect qualitative data from 26 key informants. A questionnaire was also utilized to collect quantitative data from 289 farm beneficiaries. Thematic content analysis and Atlas ti version 8 were used to analyse qualitative data, while Statistical Package for the Social Sciences (SPSS) version 25 was used for quantitative data. Ranking analysis was performed to determine factors contributing to non-performance of the farms. Majority of respondents (84.4%) agreed that farm production decreased and beneficiaries `livelihoods remained the same since restoration until 2015. Therefore, an intervention strategy was developed that included support production system, improved market access, incorporation of agricultural economics experts and engineers, to unleash agricultural potential in restituted farms to improve beneficiaries ‘livelihoods.